2016
DOI: 10.1097/j.pain.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Acute analgesic effects of nicotine and tobacco in humans: a meta-analysis

Abstract: Although animal models have consistently demonstrated acute pain-inhibitory effects of nicotine and tobacco, human experimental studies have yielded mixed results. The main goal of this meta-analysis was to quantify the effects of nicotine/tobacco administration on human experimental pain threshold and tolerance ratings. A search of PubMed and PsychINFO online databases identified 13 eligible articles, including k = 21 tests of pain tolerance (N = 393) and k = 15 tests of pain threshold (N = 339). Meta-analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 82 publications
1
85
1
1
Order By: Relevance
“…The acute analgesic effects of nicotine and tobacco in cigarettes have consistently been demonstrated in experimental animals, 41,42 albeit in human subjects the results have been controversial with the existence of paradoxical evidence. [3][4][5] Whereas some studies presented smoking as an adequate pain reliever in humans, 5,43,44 others found that they accentuate the sensation of pain 3,4,6,7 as well as cause functional impairment. 8,11 Findings of our study indicate that chronic spine-related pain patients who were managed with spinal cord stimulation do indeed report higher pain scores if they continue to smoke compared with both former smokers and lifelong nonsmokers, which goes in concordance with the majority of literature published about tobacco smoking and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute analgesic effects of nicotine and tobacco in cigarettes have consistently been demonstrated in experimental animals, 41,42 albeit in human subjects the results have been controversial with the existence of paradoxical evidence. [3][4][5] Whereas some studies presented smoking as an adequate pain reliever in humans, 5,43,44 others found that they accentuate the sensation of pain 3,4,6,7 as well as cause functional impairment. 8,11 Findings of our study indicate that chronic spine-related pain patients who were managed with spinal cord stimulation do indeed report higher pain scores if they continue to smoke compared with both former smokers and lifelong nonsmokers, which goes in concordance with the majority of literature published about tobacco smoking and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…2 One common association to chronic pain is tobacco smoking. Despite the observation that smoking may provide analgesic effects, [3][4][5] however, smokers have previously reported higher pain scores 6,7 and more associated functional impairments than lifelong nonsmokers. [8][9][10][11] According to the US Centers for Disease Control and Prevention, smoking remains the single most preventable cause of death in the United States.…”
mentioning
confidence: 98%
“…Data derived from ecological momentary assessment and experimental research paradigms further indicate that the experience of pain can increase urge to smoke and function as a proximal antecedent of smoking behavior (Dhingra et al, 2014; Ditre & Brandon, 2008), especially when individuals hold expectations for nicotine/tobacco-related pain reduction (Ditre, Heckman, Butts, & Brandon, 2010). Indeed, new meta-analytic findings show that nicotine delivered via tobacco smoke and other means (e.g., nicotine patch) can produce acute analgesic effects that may be characterized as small to moderate in magnitude (Ditre, Heckman, Zale, Kosiba, & Maisto, under review). Finally, consistent with evidence that pain can motivate smoking, there are some data to suggest that pain may impede smoking cessation.…”
Section: Bidirectional Relations Between Pain and Tobacco Smokingmentioning
confidence: 99%
“…For example, researchers have suggested that high dose nicotine replacement therapy might confer acute analgesic benefits that help to mitigate pain during the early stages of quitting (Ditre, Heckman, et al, under review). In addition, bupropion is an efficacious smoking cessation aid that is also approved by the Food and Drug Administration (FDA) for treatment of depression (Fiore et al, 2008), and there is some evidence that smokers are less likely to relapse during the early stages of a quit attempt when bupropion and nicotine replacement therapy are combined (Fiore et al, 2008; Piper et al, 2007).…”
Section: Tailored Approaches To Tobacco Dependence Treatmentmentioning
confidence: 99%
“…The relationship between the use of these two substances has a basis in the biological connection between them, as the endogenous opioid system is an underlying mechanism for several behavioral outcomes related to nicotine (i.e., nicotine craving, anxiolytic and anxiogenic effects, and nicotine withdrawal symptoms) (Nuechterlein et al 2016; Hadjiconstantinou & Neff 2011; Berrendero et al 2010). Like marijuana, nicotine is involved in anti-nociception via endogenous opioid system mediation, suggesting that nicotine is used for the self-medication of pain (Kishioka et al 2014; Ditre et al 2016); and in fact, nicotine heightens the anti-nociceptive effects of both opioids and marijuana (Kohut 2017). Several studies have documented common use patterns among tobacco, marijuana, and opioids/PPRs (Arterberry et al 2016; Abrahamsson & Hakansson 2015; Fiellin et al 2013).…”
Section: Introductionmentioning
confidence: 99%